Arabidopsis mTERF9 protein promotes chloroplast ribosomal assembly and translation by establishing ribonucleoprotein interactions in vivo. Issue 2 (5th January 2021) - Méteignier, Louis-Valentin; Ghandour, Rabea; Zimmerman, Aude; Kuhn, Lauriane; Meurer, Jörg; Zoschke, Reimo; Hammani, Kamel
Abstract: The mitochondrial transcription termination factor proteins are nuclear-encoded nucleic acid binders defined by degenerate tandem helical-repeats of ∼30 amino acids. They are found in metazoans and plants where they localize in organelles. In higher plants, the mTERF family comprises ∼30 members and several of these have been linked to plant development and response to abiotic stress. However, knowledge of the molecular basis underlying these physiological effects is scarce. We show that the Arabidopsis mTERF9 protein promotes the accumulation of the 16S and 23S rRNAs in chloroplasts, and interacts predominantly with the 16S rRNA in vivo and in vitro . Furthermore, mTERF9 is found in large complexes containing ribosomes and polysomes in chloroplasts. The comprehensive analysis of mTERF9 in vivo protein interactome identified many subunits of the 70S ribosome whose assembly is compromised in the null mterf9 mutant, putative ribosome biogenesis factors and CPN60 chaperonins. Protein interaction assays in yeast revealed that mTERF9 directly interact with these proteins. Our data demonstrate that mTERF9 integrates protein-protein and protein-RNA interactions to promote chloroplast ribosomal assembly and translation. Besides extending our knowledge of mTERF functional repertoire in plants, these findings provide an important insight into the chloroplast ribosome biogenesis.